Designing a data model for Sasaran Kerja Tahunan (SKT) system / Nurul Adilla Mohamed Taib - Mohamed Taib, Nurul Adilla (2009)
A data model is one of the crucial parts in ensuring the stability of the database of an application. Without proper or inadequate data requirements, the database may become unusable. For this reason, this research has focused on designing a data model for the Sasaran Kerja Tahunan (SKT) System. The purpose of this project is to design a data model for the Sasaran Kerja Tahunan (SKT) System so that the information related to the SKT can be managed in more systematically ways. There are 3 objectives that have been identified in this project which are identifying and name the entities, attributes, and relationships, together with any associated integrity; designing a data model for the Sasaran Kerja Tahunan (SKT) System and lastly applying indexing by using Index Organized Table in the Sasaran Kerja Tahunan (SKT) System. The processes that are involves in designing a data model are the conceptual database design, logical database design and lastly the physical database design. Thus by following all the processes, the findings and results for this research were produced. Finally, this research has been concluded by providing a conclusion and also the recommendation for the future work.